How does the flow of construction workers affect safety culture?. Issue 6 (March 2019) - Xie, Qiuhao; Yang, Gaosheng; Huang, Yan; Sun, Yuying
Abstract: Active and mature safety culture can effectively reduce the occurrence of safety accidents. However, in international projects, construction workers from different countries gather in one project, which will inevitably lead to the integration of safety culture. A bad safety culture can have a negative impact on the overall safety culture. This paper constructed a construction safety culture fusion model, and then used computer simulation technology to simulate the model. By adjusting the parameter values, the influence of the flow of construction workers on the safety culture was analyzed. It was found that the mobility of construction workers will not change the critical value of a cultural outbreak, but it will change the accumulation period before the outbreak; strengthening the cultivation of safety culture identification of construction workers can effectively prevent the impact of the poor safety culture; the new influx of safety culture first affects leaders in the project.